Development of a digital twin for a flexible air separation unit using a pressure-driven simulation approach. (August 2021) - Kender, Robert; Kaufmann, Florian; Rößler, Felix; Wunderlich, Bernd; Golubev, Dimitri; Thomas, Ingo; Ecker, Anna-Maria; Rehfeldt, Sebastian; Klein, Harald
Highlights: Definition of the term digital twin and its application for the entire plant lifecycle. Presentation of the virtual ASU, a detailed pressure-driven dynamic plant model. Introduction of a pressure-driven sieve tray column model. Presentation and discussion a plant shutdown, cold restart and a hazard analysis. Discussion of the case studies in the context of flexible plant operation. Graphical abstract: Image, graphical abstract Abstract: Currently, digitalization provides new challenges and opportunities for the process industry. A frequently used keyword in this context is digital twin . In this work, the term digital twin is defined with regard to a flexible air separation unit. Furthermore, the digital twin's core component, a highly detailed dynamic plant model, is presented. A pressure-driven approach is used as a basis for the modeling. The focus of this work is on the distillation columns. Therefore, a pressure-driven sieve tray column model is presented using design correlations for the calculation of pressure drop and both the liquid and vapor holdup. Furthermore, two industrially relevant load change scenarios are presented and discussed. A plant shutdown is simulated until a state of cold standby is reached. Then, starting from this state a cold restart is simulated. Cold standby means that the plant remains at cryogenic temperatures. Lastly, a hazard analysis is conducted.